Experiences of teenage pregnancy and its consequences on adolescent girls in rural Sindh, Pakistan - Agha, Nadia; Rind, Rahim Dad (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the challenges of teenage pregnancy experienced by adolescent girls, and its impact on their social and psychological wellbeing. Method: The qualitative study was conducted from August 5 to September 17, 2023, in different villages in northern Sindh after approval from the institutional ethical review board of Shah Abdul Latif University, Khairpur, Pakistan. Data was collected through semi-structured interviews with the subjects who had experienced teenage pregnancy in the preceding 2 years. Data was transcribed verbatim and analysed thematically. Results: Of the 37 subjects, 20(54%) were aged 19-20 years. The age at the time of marriage was 15-16 years in 22(59%) cases, and 16(43%) had received no formal education. Challenges, impact and outcome of teenage pregnancy were the 3 main themes identified on the basis of the collected data, indicating that it was a challenging experience for adolescent girls resulting in poor health outcomes. Conclusion: Community-based interventions are needed to promote female education that may put an end to adolescent motherhood. Key Words: Teenage pregnancy, Adolescent girls, Socioeconomic status, Education.